2016
DOI: 10.1002/app.43509
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐free synthesis of polyols from 1‐butene metathesized palm oil for use in polyurethane foams

Abstract: Green Polyols were synthesized from a 1-butene cross metathesized palm oil (PMTAG) using a green, solvent free epoxidation and hydroxylation pathway. The synthetic strategy was adapted to control the degree of double bond epoxidation and ultimately the hydroxyl value of the polyols. The polyols comprised diol and tetrol monomers with terminal hydroxyl groups content as high as 18 mol %, and achieved hydroxyl values between 83 and 119 mg KOH g 21 . Functional Rigid and highly flexible foams were prepared from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…28 Soy oil-based polyol (HSBP) was prepared by a ring-opening reaction of epoxidized soybean oil by distilled water using a procedure previously reported. [29][30][31] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-…”
Section: Methodsmentioning
confidence: 99%
“…28 Soy oil-based polyol (HSBP) was prepared by a ring-opening reaction of epoxidized soybean oil by distilled water using a procedure previously reported. [29][30][31] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-…”
Section: Methodsmentioning
confidence: 99%
“…Polyurethane foams with a density of 150 kgm −3 were produced from Pol‐1 and Pol‐2 (Pol‐1F and Pol‐2F, respectively) using a previously published method . The formulation recipe is provided in Table .…”
Section: Methodsmentioning
confidence: 99%
“…The chemical and physical characterisation of CMTAG, CMTAG Polyol, and CMTAG Polyol Foam were performed following the methods developed for metathesized feed stocks and the related polyols and polyurethanes . The chemical characterizations consisted of titrimetric analysis such as iodine value, acid and hydroxyl value, 1 H‐NMR, HPLC, and Fourier transform infrared spectroscopy (FTIR).…”
Section: Methodsmentioning
confidence: 99%
“…Metathesized palm oil polyols with different OH values were produced in our laboratory from this PMTAG following our previously reported procedures. , Elastomers were prepared by reacting these prepared PMTAG polyols with diphenylmethane diisocyanate (MDI, NCO content: 31.5%/wt) which was purchased from Bayer Materials Science (Pittsburgh, PA) and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…This low degree of unsaturation has limited its use for many polymer applications . Olefin cross-metathesis is a very potent transformation pathway adopted to resolve the problems associated with large quantities of dangling chains in TAG molecules to produce fine chemicals, substrates, and materials, many of which serve as or are potential petrochemical replacements. At Trent Center of Biomaterial Research (TCBR), a series of investigations have already been reported in the conversion of 1-butene cross-metathesized palm oil (PMTAG), an industrial byproduct from alpha-olefin manufacturing, into useful polyols for the preparation of rigid and flexible polyurethane foams. , The different terminal hydroxyl 1-butene metathesized palm polyols display favorable properties such as high compressive strength and good flexibility in rigid and flexible foams applications, respectively. This work sets out to investigate the transformation of different metathesized polyols into polyurethane counterparts for use in applications including, elastomers, coatings, and adhesives.…”
Section: Introductionmentioning
confidence: 99%